The Effect of Project Based Learning (PjBL) Model on Problem Solving Ability of Junior High School Students - Pratiwi, Elena Dwi Nur; Wulandari, Fitria Eka (Proceeding International Conference on Lesson Study; Vol 1 No 1 (2023): ICLS : Fostering a Learning Community Engagement Though a Lesson StudyDO - 10.30587/icls.v1i1.6518, 2023)
This study aims to determine the effect of project-based learning model on junior high school students' problem-solving skills. This research is quantitative research with One Group Pretest-Posttest Design. The subjects in this study were VIII grade students with 22 students. The technique used in sampling to determine the level of student problem solving is by distributing a questionnaire of 30 questions and then distributing it to 40 students at the local junior high school. To find out the effect of the project-based learning model on students' problem-solving skills, is done using a test, where the tests used are pre-test and post-test. The instruments used in this study are questions with problem solving indicators that have been validated by experts and declared valid and reliable for testing. The analysis used in this study was the N-Gain test using SPSS 26. The results showed the effect of the project-based learning model on student problem solving, as evidenced by the results of the N-Gain test on the pre-test and post-test which showed a value of 0.7011> 0.7000. Thus, the project-based learning model has a significant effect on students' problem solving ability with moderate criteria.